An Analytical Study of Warp Yarns Tension during the Weaving Process - Badawi, Said Sobhey (الجمعية العلمية للمصممين, 2022)
Despite the variety of weaving operations, the shed formation and its setting process are considered the most important and challenging operation ever, as it can rightly be considered the cornerstone of the whole weaving process. In this process, the warp yarns are divided into two groups at least (sometimes up to four groups in the carpet as well as narrow weaving machines). One group moves up, forming the upper layer, and the other down to form the lower layer. The created space between the two layers must be clear and clean in the sense that it takes the form of an isosceles triangle so that the warp yarns in each layer are close to each other. The side projection of the two legs of the triangle is two straight pieces, and the base of the triangle creates the shed height and it cannot be otherwise. Although the warp yarns constituting each layer are drawn in at least two heald frames and a maximum of up to twenty frames for the two layers together, the yarns of each layer must be at the same level. This can only be achieved if the tension of the warp yarns of both layers is tightly and completely defined so that the opened shed becomes valid for the weft holder to pass across (with different means of weft insertion) without any obstacles, as well as the homogeneity of the acting forces on the warp yarns during the weaving process. All of this eventually leads to the equality and homogeneity of the tensile strength of the woven fabric as a final product for any purpose of use. This may not have great importance for traditional uses of woven fabrics, but it has a great part of importance, especially in the industrial and technical use of woven fabrics. For all the aforementioned reasons, this research paper sheds the light on this important point in the field of the textile industry, which is the difference in the yarns' tension rates during operations. This is a frequent occurrence in all stages of the textile industries, whether in the different spinning processes and the procedures of weaving preparation such as winding, warping, etc., and the processes of weaving, warp, and weft knitting. The research paper is concerned with the study and analysis of the forces affecting the warp yarns throughout the full cycle of a complete repeat of fabric construction. An analytical research study to determine the reasons for the change in the tension rates affecting the warp yarns. As well as trying to develop applied technical solutions to solve the obstacles that occur during the weaving process, to increase the quality of the woven product under the required quality rates. Clarify and analyze the practical and scientific reasons for this problem, while laying the technical foundations for the possibility of solving it in the future in the next research papers.
Keywords: صناعة النسيج -- عمليات الغزل -- تقنيات النسيج